المركز القانوني للمحكم في التشريع الجزائري - بروال, زين الدين (My University, 2018)
أن المحكم له دور أساسي في العملية التحكيمية وهو المحرك الرئيسي لها، وأن هذا المحكم يمتاز بشروط قبل توليه المهمة التحكيمية ومنها ما نص عليه القانون كوجوب تمتعه بالأهلية المدنية، ويجب أن يكون المحكم شخصا طبيعيا، وأن يتمتع بالحياد والاستقلال أثناء تأديته لمهامه. وسلطات المحكم تتمثل في تسيير اجراءات التحكيم، وذلك بمعرفة النطاق القانوني لسلطة المحكم من خلال التعريف على اختصاصه بالنزاع، وكذلك العمليات التي يقوم بها وقد تكون سلطات المحكم عند تفسيره لحكمه التحكيمي، وكذلك تصحيحه لحكمه.That the arbitrator has an essential role in the arbitration process and is the main driver of the arbitration, and that the arbitrator has pre-requisites before taking up the arbitral assignment, including the provisions of the law as a civil suit. The arbitrator must be a natural person and be impartial and independent in the performance of his functions. The powers of the arbitrator are to administer the arbitral proceedings by knowing the legal scope of the authority of the arbitrator by defining his jurisdiction over the dispute, as well as the operations that he may undertake, and the powers of the arbitrator when interpreting his arbitral award, as well as rectifying his judgment.
قانون أعمال
Keywords: المحكم - العملية التحكيمية - الأهلية المدنية; arbitrator - essential role - Civil eligibility